Corporate communication : critical business asset for strategic global change - Goodman, Michael B., 1949-; Hirsch, Peter B., ....- (New York (N.Y.) : Lang, 2015)
The communication role in organizations has changed, just as the nature of organizations has changed in response to the explosion of new communication technologies as well as global networks within organizations. Communication is more complex, strategic, and vital to the health of the organization than it used to be, and it will become increasingly important in the information-driven economy. This book builds upon the authors' 2010 book, Corporate Communication: Strategic Adaptation for Global Practice, which focused on the role of the communicator. This volume examines, analyzes, and illustrates the practice of corporate communication as a critical business asset in a time of global change. It looks at the major communication needs in the lifecycle of organizations: M&A (mergers and acquisitions), structural change, culture change, innovation, new leadership, downsizing, global expansion, competition, ethical decision-making, political action, and employee engagement. These are all significant value-creating, and potentially value-destroying, events in which corporate communication, if used correctly, functions as a critical and strategic business asset.
Includes bibliographical references and index.
Keywords: Communicatie -- Organisaties; Communication in management; Communication in organizations; Corporate culture